99.8k views
2 votes
I need to know the bottom part pls

I need to know the bottom part pls-example-1
User GuyZ
by
5.6k points

1 Answer

0 votes

Answer:

Explanation:

j + d = 895

j = d + 177

Let us substitute the second equation into the first one for j.

So the first equation can be rewritten as (d + 177) + d = 895

=> 2d + 177 - 177 = 895 - 177

=> 2d = 718

=> 2d/2 = 718/2

=> d = 359

=> j = 359 + 177

=> j = 536

Checking your answer:

j + d = 536 + 359 = 895

User Dpoetzsch
by
5.4k points